2016
DOI: 10.1080/00365513.2016.1187765
|View full text |Cite
|
Sign up to set email alerts
|

A promising marker in early diagnosis of septic acute kidney injury of critically ill patients: urine insulin like growth factor binding protein-7

Abstract: Admission urine IGFBP7 levels and following its course in ICUs can be used as a promising new biomarker for the early diagnosis of septic AKI development without being affected by sepsis itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In congruence with our findings, A prospective multicentre observational study of 94 babies, (22) detected that Patients with AKI had substantially increased urine IGFBP-7*TIMP-2 levels. Other researchers (23) reported that IGFBP-7*TIMP-2 may reliably assess AKI development in neonates after cardiac operation. IGFBP-7*TIMP-2 usefulness in high-risk patients having major noncardiac surgery has also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In congruence with our findings, A prospective multicentre observational study of 94 babies, (22) detected that Patients with AKI had substantially increased urine IGFBP-7*TIMP-2 levels. Other researchers (23) reported that IGFBP-7*TIMP-2 may reliably assess AKI development in neonates after cardiac operation. IGFBP-7*TIMP-2 usefulness in high-risk patients having major noncardiac surgery has also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ], demonstrated that urinary [IGFBP-7]*[TIMP-2] was significantly higher in patients with AKI. It can effectively predict the occurrence of AKI following cardiac surgery in infants [ 20 ].…”
Section: Discussionmentioning
confidence: 99%